Toxicidade do uso tópico de tacrolimo ao endotélio de córnea de coelhos - Cristiana de Moraes Ramalho (2010)
Objective: to evaluate the toxicity of tacrolimus (FK506) in the corneal endothelium of rabbits when used topically in the form of ointment. Material and method: the corneas of 26 New Zealand rabbits were divided into three groups. In group 1, the corneas of the right eye of 13 animals were treated with Tacrolimus ointment at a concentration of 0.03% (Protopic®) twice daily for 15 days. In group 2, the corneas of the right eye of 13 animals were treated with Tacrolimus ointment at a concentration of 0.1% (Protopic®) twice daily for 15 days. The Group 3 (control) was formed by the cornea of the left eye of all animals. After 15 days the rabbits were sacrificed with intravenous overdose of pentobarbital. Ten animals from each group were evaluated using digital photographs taken from the optical microscope with the endothelium stained with alizarin red S and three animals from each group were examined by scanning electron microscopy. The corneal thickness, pachymetry, was measured before and after the period of 15 days of the used the medication. Endothelial damage was assessed by measuring the cellular area, endothelial cell density, variation coefficient and number of sides of cells both on light microscopy and scanning electron microscopy with morphometric evaluation of endothelial cell, and the assessment of central corneal thickness by pachymetry ultrasound. Results: the central corneal thickness and extent and timing of endothelial cells by optical microscopy with cells stained with alizarin red S and by scanning electron microscopy did not change significantly when compared with control after topical tacrolimus ointment in two concentrations (0.03% and 0.1%) for a period of 15 days. Conclusion: the use of topical tacrolimus ointment in two different concentrations did not induce changes in endothelial cells of rabbit cornea.